ACQUISITION STRATEGY REVIEW DURING THE COVID-19 PANDEMIC (CASE STUDY: OF PT SARANA MENARA NUSANTARA TBK'S (TOWR)) - Gusmanto, Bambang; Perangin Angin, Matius; Saputra, Dana Handika Dwi; Hardiansyah, Hardiansyah (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the effectiveness of PT Sarana Menara Nusantara Tbk's (TOWR) acquisition strategy for PT Solusi Tunas Pratama Tbk (SUPR) in the context of the COVID-19 pandemic. The pandemic has had a significant impact on the telecommunications sector, increasing public demand for better digital communication services, but also presenting challenges in the form of uneven infrastructure. The study employs a qualitative approach, incorporating a literature review and a SWOT analysis, to assess the internal and external factors influencing acquisition decisions and their impact on company competitiveness. The results show that the acquisition strategy succeeded in significantly increasing infrastructure capacity, with the number of TOWR telecommunications towers expanding from 21,575 to approximately 28,000 units, and share ownership reaching 99.96%. Key factors for the success of this acquisition include a strong market position, financial stability, competent human resources, and external opportunities such as increasing demand for digital services and government policies. However, the study also identified strategic risks that require attention, such as high transaction costs and the complexity of operational integration. This study recommends that companies conduct in-depth analysis before the acquisition process and implement comprehensive risk management. Theoretically, this research contributes to the understanding of the effectiveness of acquisition strategies in pandemic crises